👤

2 la puterea 2 la puterea3÷4 la puterea 3 + 3 la puterea 2 la puterea 2 ÷ ( 2 la puterea 6 -6 la puterea 2-36 la puterea 0​

Răspuns :

(2²)³ : 4³ + (3²)² : (2⁶ - 6² - 36⁰) =

2⁶ : 2⁶ + 3⁴ :(64 - 36 - 1) =

1 + 81:27 =

1 + 3 = 4

Maas10

Răspuns:

[tex](2 {}^{2}) {}^{3 } \div 4 {}^{3} +( 3 {}^{2} ) {}^{2} \div (2 {}^{6} - 6 {}^{2} - 36 {}^{0} ) \\ = 2 {}^{6} \div 2 {}^{6} + 3 {}^{4} \div (64 - 36 - 1) \\ = 1 + 3 {}^{4} \div 27 \\ = 1 + 3 {}^{4} \div 3 {}^{3} = 1 + 3 {}^{4 - 3} = 1 + 3 {}^{1} = 1 + 3 = 4[/tex]